2008
DOI: 10.1038/cr.2008.138
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of human umbilical cord blood cells on diebetic mice

Abstract: Human adult stem cell research has been paid more attention because of the compelling ethical and legal issues surrounding human embryonic stem cells. Mononuclear cells from human umbilical cord blood (MNCs) have been showed to have plasticity. In our study, human umbilical cord blood MNCs could survival in diabetic mice without using immuno-suppressive drugs and could decreased serum glucose levels at definite time period. To observe the therapeutic effect on diabetic mice of mononuclear cell from human umbil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…This result comes in conformity with that reported by others [5] as they demonstrated that after 4 days of HUCB mononuclear cells transplantation into STZ diabetic mice, serum glucose level was significantly decreased in comparison with pre-transplantation. In another study [6] diabetic mice were treated with human bone marrow stromal cells and they demonstrated that human bone marrow stromal cells lowered blood glucose levels in the treated diabetic mice relative to untreated controls (330.12 mg/dl± 20.16 SE vs 500 mg/dl±44.1 SE, P=0.0019).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…This result comes in conformity with that reported by others [5] as they demonstrated that after 4 days of HUCB mononuclear cells transplantation into STZ diabetic mice, serum glucose level was significantly decreased in comparison with pre-transplantation. In another study [6] diabetic mice were treated with human bone marrow stromal cells and they demonstrated that human bone marrow stromal cells lowered blood glucose levels in the treated diabetic mice relative to untreated controls (330.12 mg/dl± 20.16 SE vs 500 mg/dl±44.1 SE, P=0.0019).…”
Section: Discussionsupporting
confidence: 95%
“…We found that the improvement of hyperglycemia was reversible and relapse occurred after 3 weeks, this finding was reported by many investigators [5,8] as they demonstrated that after 14 days of improvement, serum glucose level was returned to the pre-transplantation level. Others reported that the relapse occurred in 40% of the transplanted animals after 12 weeks.…”
Section: Discussionsupporting
confidence: 68%
“…Another study by Zhang and associates [34] also provides evidence in support of the observations of Zhao et al [17], who observed a transient blood glucose-lowering effect of HUCB mononuclear cells in streptozotocin-induced diabetic mice. These investigators injected via tail vein 2x10 6 cells into diabetic mice, and blood glucose as well as insulin levels were measured 4 days later.…”
Section: Animal Studiesmentioning
confidence: 64%